(untitled) (Research, Society and Development, 2022)
The objective of this work was to investigate the viability of the production of Self-Adhesive Mortars (AAA) as an initial phase for CAA production, performing the replacement of sand ground glass residue proportions of 5%, 10%, 15%, 20% and 30% by mass, using as mineral addition to Active Silica (AS) and as a superplasticizer chemical additive (SPA). The search for solutions to address the growing demand for civil construction and sustainability in the exploitation of natural resources involves the search for new renewable sources and the use of waste, especially those that are not yet satisfactorily absorbed by the recycling industry as glass. Widely used worldwide, concrete and other cementitious composites are excellent for the absorption of residues from various origins and have been improved in recent decades, as for Self-Adensable Concrete (CAA). To achieve the objectives proposed in this study, mortar tests were performed in the fresh and hardened states, analysis of images generated by scanning electron microscopy, and investigation of the occurrence of Alkali-Aggregate Reaction. The results showed it is feasible to use glass residue as a partial substitute for the production of CAA, since the self-adhesive mortar produced met the requirements in a fresh state and had, in most, their mechanical properties improved, and can even meet structural applications, such as reinforcements and repairs.